2011
DOI: 10.3415/vcot-10-05-0070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro serial antibiotic elution from meropenem-impregnated polymethylmethacrylate beads after ethylene oxide gas and autoclave sterilization

Abstract: Summary Objectives: To determine the elution properties of meropenem and to compare the elutions of meropenem-impregnated polymethylmethacrylate (PMMA) beads without sterilization (P-M-C) to those sterilized with steam (P-M-A) and ethylene oxide gas (P-M-EO). Methods: A commercial bead mould was used to produce four groups of beads: one group without antibiotic (negative control), and three groups of meropenem-impregnated beads: P-M-C, P-M-A, and P-M-EO. The beads were placed in a phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, only 15 to 30 g cement was tested and higher amounts that are typically used in clinical practice may lead to increased polymerization temperatures. Báez et al reported that meropenem-impregnated PMMA beads were not suitable for applications after autoclave sterilization, since zone growth inhibition was no longer observed after autoclaving [ 23 ]. They conclude that the exothermic reaction combined with the exposure to 121 °C for 15 min during autoclaving rendered meropenem incorporated into the cement bio-actively inert.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 15 to 30 g cement was tested and higher amounts that are typically used in clinical practice may lead to increased polymerization temperatures. Báez et al reported that meropenem-impregnated PMMA beads were not suitable for applications after autoclave sterilization, since zone growth inhibition was no longer observed after autoclaving [ 23 ]. They conclude that the exothermic reaction combined with the exposure to 121 °C for 15 min during autoclaving rendered meropenem incorporated into the cement bio-actively inert.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of calcium phosphates is that they could be sterilized by a variety of techniques, including γ-irradiation, gas plasma, supercritical carbon dioxide, or even steam autoclaving (in the case of hydroxyapatite), without causing adverse effects to their structure and properties. By contrast, in general there is currently no established sterilization procedure for polymers that does not modify their structure to some degree, due to (1) physical deformations and chemical changes—scission and cross-linking that occur upon autoclaving, 113 alongside practically inevitable degradation of an encapsulated drug 114 ; (2) surface chemistry modifications that occur upon the application of ethylene oxide, hydrogen peroxide, or ozone 115 ; (3) bulk structural changes and a decrease in the molecular weight that occur during γ-irradiation, 116 while a difficult regulatory path is posed before novel or nontraditional sterilization methods.…”
Section: Advanced Drug Delivery Platforms In the Research Stagementioning
confidence: 99%